Experimental study of room-temperature indentation viscoplastic 'creep' in zirconium. Issue 24 (22nd August 2016) - Storer, S. C.; Fitzpatrick, M. E.; Hainsworth, S. V.; Rist, M. A.
Abstract: In this paper we have studied the mechanisms of so-called 'indentation creep' in a zirconium alloy. Nanoindentation was used to obtain strain rate data as the sample was indented at room temperature, at a homologous temperature below that for which creep behaviour would be expected for this material. A high value of strain rate was obtained, consistent with previous work on indentation creep. In order to elucidate the mechanism of time-dependent deformation, a load relaxation experiment was performed by uniaxial loading of a sample of the same alloy. By allowing relaxation of the sample from a peak load in the tensile test machine, a similar stress exponent was obtained to that seen in the nanoindentation creep test. We conclude that for metals, at temperatures below that at which conventional creep will occur, nanoindentation 'creep' proceeds through deformation on active slip systems that were initiated by prior loading beyond the plastic limit. It is therefore more appropriate to describe it as a viscoplastic process, and not as creep deformation.